The effect of 12-week of pyramidal and polarized training intensity distribution in national elite adolescent swimmers - Arroyo-Toledo, J. J.; Sortwell, A. D.; Clemente-Suarez, V. J. (Journal of Swimming Research, 2020)
This study aimed to analyze modifications in swimming performance, maximal oxygen uptake, heart rate, and anthropometric variables after a 12-weeks of training involving a pyramidal or polarized training intensity distribution. 12 volunteer female swimmers were recruited from a nationally competitive program. They were divided into a control group (21.58 ± 2.93 kg/m²; 166.50 ± 2.08 cm; 59.70 ± 7.19 kg) and experimental group (20.46 ± 2.19 kg/m²; 166.20 ± 4.32 cm; 54.24 ± 3.10 kg). The control group performed a pyramidal training intensity distribution and the experimental group performed a polarized training intensity distribution. Pre and post measures included body composition, maximal oxygen uptake, 100m (t100c) and 800m (t800c) freestyle performance. Pyramidal distribution significantly decreased t800c, fat mass and increased maximal oxygen uptake and fat free mass. Polarized distribution decreased t100c, fat mass and increased maximal oxygen uptake and fat free mass. The modifications in t100c were significantly higher in polarized distribution and t800c higher in pyramidal as well as the decreases in fat mas and the increases in fat free mass. The results demonstrated that the pyramidal and polarized training intensity distributions produced different improvements in swimming performance, body compositions and maximal oxygen uptake of female adolescent swimmers.